What social determinants will cause ethical challenges in geriatric care? Comments from South Africa - Laetus Lategan; Gert van Zyl; Willem Kruger (AOSIS, 2023)
Background: Social determinants are defined as those nonmedical factors that influence health. Their influence is especially evident in vulnerable communities, such as the geriatric one. However, which social determinants will cause ethical challenges in geriatric healthcare in South Africa are not yet confirmed. Objective: This study first identified which social determinants influence geriatric care. The study then established which of these social determinants raises ethical challenges in geriatric care. Methods: Twenty statements were identified from the literature review and were grouped into 3 indexes, focusing respectively on i) a general view on public health and social determinants; ii) social determinants influencing geriatric people's health; iii) the consequences of social determinants on geriatric people's health. The rating was based on presenting the statements employing a 5- point Likert scale. Results: The rating of statements confirmed the generally accepted view that social determinants impact geriatric people's health. The responses to the statements were an additional confirmation that the quality and access to healthcare services influence geriatric care and lead to ethical challenges. Matters such as corruption, limited resources, and the COVID-19 pandemic contribute to the influence of social determinants and the expected but failed ethical behavior toward the geriatric community. Conclusion: The geriatric community is vulnerable because of the ongoing social factors that have a negative impact on health, of which healthcare quality and provision are significant contributing factors. These factors contribute to ethical challenges in healthcare for the geriatric community.